Letrozole-Induced Very Early Systemic Sclerosis in a Patient With Breast Cancer: A Case Report - Gabriel POKHAI,; Rino BUZZOLA,; Adriana ABRUDESCU, (Archives of Rheumatology, 2014)
Aromatase inhibitors (AIs) are standard therapy for post-menopausal women with breast cancer. The use of AIs has been strongly associated with musculoskeletal symptoms and with various autoimmune conditions recently. Systemic sclerosis (SSc) is a connective tissue disorder of unknown etiology which may present with a broad range of clinical manifestations. In SSc, matrix deposition by activated fibroblasts leads to vasculopathy, systemic fibrosis, and end-organ damage. Skin, kidneys, pulmonary and gastrointestinal systems may be affected. Very early SSc can be diagnosed in patients with Raynaud's phenomenon and puffy fingers as well as through autoantibodies and nailfold capillaroscopy. These symptoms are highly predictive of the further development of definite SSc. In this article, we report an unusual case of a 61-year-old female breast cancer with a very early-onset SSc with bilateral stiffness of the hands, Raynaud's phenomenon, puffy fingers, dilated nailfold capillaries and positive anticentromere-B antibody titers after undergoing AI therapy with letrozole. Substitution of letrozole with exemestane followed by eventual discontinuation of AI therapy appears to relieve symptoms. To the best of our knowledge, this is the first report suggesting a link between AI use and SSc. We suggest that AI use may induce SSc, or at least, exacerbate existing very early SSc in post-menopausal patients with breast cancer.